Four elevational range extensions of birds of the Western Andes of Colombia and northwestern Ecuador: Cuatro extensiones de las distribuciones elevacionales de aves de la Cordillera Occidental de Colombia y el noroccidente de Ecuador (Ornitología Colombiana, 2021)
Research suggests that bird elevational ranges may be shifting upslope because of deforestation, habitat fragmentation or climate change. I present observations of four bird species that were encountered at a private reserve in Ecuador more than 300 meters above their known maximum altitudes in Colombia and Ecuador, including two that were recorded at altitudes higher than globally recorded maximums.